AMBIVALENSI KOTA DEMOKRASI DALAM FILSAFAT POLITIK AL FARABI STUDI KRITIS MADINAH AL FADHILAH AL FARABI - Yasin, Mohammad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2013)
It is fashionable nowadays to be democratic; prompted by the desire to portray Islam as a modern ideology and a progressive government system, they have interpreted Islamic political and juridical theory in democratic terms. In short, some people assumed that democracy is the only good government system. But, in few centuries ago, al-Faraby criticized democracy as a bad government system. Al Farabi said democracy is a good system between bad systems, he proposed “the prime city (Madinah al- Fadlilah)” system. The prime city is the post democracy system, giving direction to the people to achieve ‘highest happiness’. But in other hand Al Farabi said that democracy possible to grow up men of excellent, more civilized, more populated, more productive and more perfect. It is also possible to glean from it certain parts of the virtuous city. Thus it may include philosophers, rhetoricians, and poets dealing with all kinds of things. Al Farabi seems to tell us that democracy is the most favourable for the founding of a Virtuous city. Al Farabi never tell us how the virtuous city may arise from the city of pigs; but he tells us how we may glean the various city from democracy. Al Farabi mentioned that democracy is bad system, but he also said that a virtuous city can rise from democracy city. According to me, Al Farabi inconsistent on his theory of democracy and it open to be criticized. This article will explain the Al Farabi’s theory of democracy deeply and criticize it. Keywords: Democracy, City, State, and Madinah-al-Fadhilah